After dark : the nocturnal urban landscape and lightscape of ancient cities - Gonlin, Nancy; Strong, Meghan E. (University Press of Colorado, 2022)
"After Dark explores the experience of nighttime within ancient urban settings. Contributors present evidence related to how ancient people manipulated and confronted darkness and night in urban landscapes, advancing our knowledge of the archaeology of cities, the archaeology of darkness and night, and lychnology (the study of ancient lighting devices)"--